Socialization in Improving the Quality of English Teaching at SMA Negeri 3 Pematangsiantar: A Case Study on TOEFL - Pakpahan, Surya Ningsih; Situmorang, Gracela Emylia; Sidabutar, Yohana Anggita; Gultom, Destri Yani Puspita Sari; Rajagukguk, Mutiara; Sinaga, Yanti Kristina; Sinurat, Bloner; Munthe, Melda Veby Ristella (Pengabdian Masyarakat Sumber Daya Unggul, 2024)
This socialization activity aims to introduce and provide knowledge and insight to students at the SMA Negeri 3 Pematangsiantar about the TOEFL test. The socialization activity regarding the introduction of TOEFL to vocational school students, was held on January 18, 2024. Participants in this socialization activity were 11 grade vocational school students totaling 31 people. Participants gain new knowledge about the TOEFL test. There were three phases in conducting this socialization, namely preparation, implementation and evaluation. The results obtained from this socialization activity are, they know and understand what the TOEFL test is, types of questions in the TOEFL test, number of questions tested in the TOEFL test, duration and time for completing TOEFL questions, tips for studying TOEFL and also the importance of TOEFL test. This socialization can also increase student's motivation to study English more seriously. They can view the TOEFL exam as a challenge to overcome and as a first step towards success in their future academic and professional careers. From the results above it can be concluded that this activity gave a positive impact for the students in the future.